From tradition to technique: perspectives and realities of felling and burning agriculture in Amazon (Research, Society and Development, 2021)
The felling and burning system is still practiced in the Amazon, contributing to environmental destruction. The objective was to present the perspectives and realities of slash and burn agriculture in the Amazon, as well as their relations involved. A bibliographic survey was used to carry out the study. Farmers persist in this system, as it is low cost and easy to adopt, due to the low fertility of most soils in the Amazon region, the high cost of fertilizers and correctives. The main current focuses of burning in the Amazon are associated with agriculture, especially on a family scale. The fires practiced cause damage to the environment, fauna and flora. This system, proves to be unsustainable still present in the agricultural environment, mainly in family farming in the Northern region of Brazil, an aggravating factor for the local fauna and flora.